A test on audit tenure, auditor size, independence of audit committee and the issuance of going concern opinion - Shafie, Rohami; Md Yusof, Mohd 'Atef; Md Hussain, Md Hairi (Faculty of Accountancy, 2004)
The issue of audit tenure has been discussed since four decades age. Nowadays, due to the recent corporate scandals in the United States, the issue is discussed together with auditor independence that led to companies’ demise. Mandatory audit rotation debates come from the arguments that long audit tenure would create cosy relationship between auditors and clients and thus would lead to audit reporting failure such as in the case of bankruptcy. Therefore, this study attempts to investigate the situation in Malaysia whereby no empirical study using archival data has been done. Specifically, the current study examines the impact of audit tenure on the issuance of going concern opinion.